Neuroimmunological approach for evaluation of viral measles, mumps and rubella triple vaccine - Castillo González, William; Cruz Quevedo, Mileydis; Rodríguez Pérez, José Alejandro; Barrios Lamoth, Eneida; González Losada, Cristóbal; Dorta Contreras, Alberto Juan (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: During the neuroinflammatory processes there are a poly-specific and polyclonal activation in the cerebrospinal fluid. It means that there can be quantified antibodies against all the components of the vaccines may have received. Objective: To evaluate the immune response against measles, mumps and rubella in vaccinated pediatric patients. Methods: All the serum and cerebrospinal fluid (CSF) paired samples from pediatric patients with neurological symptoms, that were submitted to hospitals from Havana City and were performed a lumbar puncture, were collected. Serum and CSF IgG, albumin were measured by immune-diffusion techniques using NOR and LC Partigen Immunoplates (Siemens, Marburg) and specific antibodies against measles, mumps and rubella were quantified by ELISA kits (Enzygnost, Siemens, Marburg). Reibergrams were employed in order to determine if there was IgG intrathecal synthesis. Later on, antibody index against the specific virus were calculated. Results: In all the neuroimmune inflammation process were found antibody index against measles, mumps and rubella in a different ample confidence variation among the different virus. Antibodies against mumps are significantly different from the other ones. It could be due to a natural different immune response or due to a deficient vaccine quality lot. Also it was possible to identify six pediatric patients that had no immune antibody index at all. It coincides with a transient hypogammaglobulinemia of infancy in such patients. Conclusions: This neuroimmunological approach can be used to evaluate the immune status in pediatric population.